1995
DOI: 10.3109/00207459509015301
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic mechanisms in gilles de la tourette's syndrome

Abstract: Gilles de IaTourette syndrome (GTS), a chronic, familial, neuropsychiatric disorder of unknown etiology. is characterized clinically by the presence of motor and vocal tics that wax and wane in seventy over time and by the occurrence of a variety of neurobehavioral disturbances including hyperactivity, self-mutilatory behavior. obsessive compulsive behavior, learning disabilities, and conduct disorder. Pharmacological studies suggest that the tics of GTS result from dysfunction of monoaminergic systems, more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recently, it has been reported that extracranial pulsed application of picotesla flux electromagnetic fields (EMFs) produced recurrent episodes of yawning in two pediatric patients with Tourette's syndrome (Sandyk, 1995; in press). Recurrent yawning has been ob-Int J Neurosci Downloaded from informahealthcare.com by Freie Universitaet Berlin on 12/04/14…”
Section: R Sandykmentioning
confidence: 99%
“…Recently, it has been reported that extracranial pulsed application of picotesla flux electromagnetic fields (EMFs) produced recurrent episodes of yawning in two pediatric patients with Tourette's syndrome (Sandyk, 1995; in press). Recurrent yawning has been ob-Int J Neurosci Downloaded from informahealthcare.com by Freie Universitaet Berlin on 12/04/14…”
Section: R Sandykmentioning
confidence: 99%
“…Some researchers consider the exposure to MF as a potential risk factor for neurodegenerative diseases [10], whereas others deny it [11]. Furthermore, there is evidence of a beneficial effect of MF on the cognitive processes and the visual memory in patients with AD [12,13]. The MF using opens new possibilities of treating this severe disease.…”
Section: Groups Of Animalsmentioning
confidence: 99%